Kelimpahan Foraminifera Bentonik Besar - Diva Putri Faulina; Lili Fauzielly (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
The aim of this research is to determine the abundance of large benthic foraminifera in the study area. This research method is descriptive quantitative. There were 4 thin section samples used in this research, these samples came from cores at a depth of (36m – 39m). The results of the research showed that from the four incisions, 7 variations of large benthonic foraminifera genera were found, including, Spiroclypeus, Alveolina, Trillina hawchini, Cycloclypeus, Miogypsina, Heterostegina, and Assilina. Analysis of the abundance of large benthic foraminifera was carried out based on identification of the presence of foramnifera in each thin section sample. It is known that the thin section sample with the highest abundance of large benthonic foraminifera was in the code section sample (38m – 39m) with a total abundance of 9 individuals, consisting of 4 different genera of large benthonic foraminifera. In conclusion, the abundance of large benthic foraminifera tends to increase with increasing core depth. Keywords: Large Benthonic Foraminifera, Genus, Abundance, Rajamandala